2015
DOI: 10.1080/08897077.2013.835763
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Caffeine in the Alcohol Consumption Behaviors of College Students

Abstract: Although alcohol-caffeine consumption was associated with heavier drinking characteristics compared with alcohol-only consumption, overall alcohol consumption patterns were similar between users of various alcohol-caffeine combinations. Future examinations should assess alcohol in combination with a variety of caffeine sources to determine whether energy drinks present a unique risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Cobb, Nasim, Jentink, and Blank () surveyed 1,174 U.S. undergraduate students. Motives for consumption were recorded for (a) premixed AMED drinks, (b) self‐mixed AMED drinks, and (c) other nonalcoholic caffeinated beverages mixed with alcohol.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cobb, Nasim, Jentink, and Blank () surveyed 1,174 U.S. undergraduate students. Motives for consumption were recorded for (a) premixed AMED drinks, (b) self‐mixed AMED drinks, and (c) other nonalcoholic caffeinated beverages mixed with alcohol.…”
Section: Resultsmentioning
confidence: 99%
“…The items "to get drunk" and "it feels like it reduces the negative effects of alcohol" were significantly more often endorsed for AMED consumption, whereas the motive "it feels like I can drink more alcohol" was significantly more endorsed for mixing alcohol with other beverages (18.9%). Cobb, Nasim, Jentink, and Blank (2015) surveyed 1,174 U.S. undergraduate students. Motives for consumption were recorded for (a) premixed AMED drinks, (b) self-mixed AMED drinks, and (c) other nonalcoholic caffeinated beverages mixed with alcohol.…”
Section: Droste Et Al 2014 Examined Motives For Amed Consumption Inmentioning
confidence: 99%
“…13 The consumption of EDs among adolescents and young adults is especially troubling since this activity has been linked to high risk behaviors such as smoking, drinking, illicit drug use, unsafe sexual practices, and fighting. [14][15][16] In addition, recent studies have linked the consumption of EDs to poor dietary habits, as well as unhealthy behaviors such as video gaming, use of unhealthy weight control programs, and substance abuse. 17,18 In addition, the combination of EDs and alcoholic beverages 15,19,20 has led to increased alcohol intake and, consequently, alcoholrelated adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, 74% of participants in this study consumed 8-ounce, cans which raises the question of how many are consuming energy drinks with alcohol. And, of course, alcohol has been shown to lead to addictive behaviors (Cobb et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…College students' consuming alcohol-caffeine beverages (energy drinks) showed heavier drinking when compared to those consuming just alcohol (McIlvain et al, 2011). The combination of energy drinks with alcohol has been described as a release from stress among college students and has been correlated with addictive responses (Cobb, Nasim, Jentink, & Blank, 2015). Pettit and DeBarr (2011) concluded that there was a correlation between energy drinks and perceived stress.…”
Section: Literature Reviewmentioning
confidence: 98%